Ectopic Spleen in the Pelvis: A Case Report - Algheryani, Abdelhakim; Muftah Younis, Sarah (Libyan International Medical University Journal, 2023)
Ectopic spleen is a rare clinical condition characterized by splenic hypermobility caused by elongation or mal-development of the suspensory ligaments leading to the presence of spleen outside of its normal position. It is most commonly presented in children younger than 1 year and in females of childbearing age.A 34-year-old woman underwent magnetic resonance imaging (MRI) after suspicion of uterine fibroids. The patient only complained of a painless lower abdominal mass. MRI revealed the enlarged spleen in the pelvic area, measuring 17 × 4.6 cm, suspended by elongated, dilated, and tortuous pedicle in the absence of the spleen in its normal position. Multiple factors could be attributed to the development of an ectopic spleen. These include the following: (1) congenital anomalies in the development of the dorsal mesogastrium and the absence or malformation of the normal splenic suspensory ligaments, (2) acquired conditions such as splenomegaly and pregnancy. An ectopic spleen can present in a variety of ways clinically. It might pass unnoticed throughout life. However, ectopic spleen should be considered in the differential diagnosis of patients presented with an abdominal mass. Imaging modalities are used to make a final diagnosis. The treatment choice for an ectopic spleen is splenopexy. Splenectomy is only necessary in case of an infarction.
Keywords: ectopic; magnetic resonance imaging; mass; pelvis; spleen